OPTIMIZING VISUALLY IMPAIRED ABILITY TO READ TACTILE PICTOGRAM THROUGH TEXTURE DESIGN - Fadhlillah, Fariz (Visualita Jurnal Online Desain Komunikasi Visual, 2021)
ABSTRACT. This experiment aims to optimize the visually impaired ability when reading tactile pictograms through texture design. Experiment was motivated by two previous studies results by authors show that the visually impaired need a tool to make the reading process more efficient. Overall, the visual semiotic was used to adapt the Space-Time-Curve (STC), Tabrani's visual language theory, as a texture media design system. The design result produces media textures with size composition differences. The media was tested on 20 visually impaired people directly with quantitative analysis technique. The results show that the design system for media textures is not able to optimize visually impaired reading. In general, it concluded that the visually impaired do not perceive a system without memory regarding its variable mechanism as a whole.